LDHA upregulation independently predicts poor survival in lung adenocarcinoma, but not in lung squamous cell carcinoma. (14th May 2018) - Yu, Chengyong; Hou, Liyan; Cui, Hailing; Zhang, Liyan; Tan, Xiaodong; Leng, Xuejiao; Li, Yingbo
Aim: To investigate the potential prognostic value of LDHA in lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSC).Patients & methods: Molecular, clinicopathological and survival data in Cancer Genome Atlas-Lung Cancer were obtained for secondary analysis.Results: LDHA expression was significantly upregulated in both LUAD and LUSC compared with normal lung tissues. LUSC tissues had even higher LDHA expression compared with LUAD tissues. Increased LDHA expression was an independent prognostic indicator in terms of overall survival (hazard ratio: 1.547, 95% CI: 1.253–1.911; p < 0.001) and recurrence-free survival (hazard ratio: 1.486, 95% CI: 1.161–1.900; p = 0.002) in LUAD, but not in LUSC.Conclusion: LDHA expression might only serve as an independent prognostic indicator of unfavorable overall survival and recurrence-free survival in LUAD, but not in LUSC.